Reproductive phenology of Melastomataceae species with contrasting reproductive systems: contemporary and historical drivers. (16th July 2017) - Brito, V. L. G.; Maia, F.R.; Silveira, F. A. O.; Fracasso, C. M.; Lemos‐Filho, J. P.; Fernandes, G. W.; Goldenberg, R.; Morellato, L. P. C.; Sazima, M.; Staggemeier, V. G.
Abstract: Flowering and fruiting are key events in the life history of plants, and both are critical to their reproductive success. Besides the role of evolutionary history, plant reproductive phenology is regulated by abiotic factors and shaped by biotic interactions with pollinators and seed dispersers. In Melastomataceae, a dominant Neotropical family, the reproductive systems vary from allogamous with biotic pollination to apomictic, and seed dispersal varies from dry (self‐dispersed) to fleshy (animal‐dispersed) fruits. Such variety in reproductive strategies is likely to affect flowering and fruiting phenologies. In this study, we described the reproductive phenology of 81 Melastomataceae species occurring in two biodiversity hotspots: the Atlantic rain forest and the campo rupestre . We aim to disentangle the role of abiotic and biotic factors defining flowering and fruiting times of Melastomataceae species, considering the contrasting breeding and seed dispersal systems, and their evolutionary history. In both vegetation types, pollinator‐dependent species had higher flowering seasonality than pollinator‐independent ones. Flowering patterns presented phylogenetic signal regardless of vegetation type. Fruiting of fleshy‐fruited species was seasonal in campo rupestre but not in Atlantic rain forest; the fruiting of dry‐fruited species was also not seasonal in both vegetation types. Fruiting showed a low phylogenetic signal, probably because the influence of environment and dispersal agents on fruiting time is stronger than the phylogenetic affinity. Considering these ecophylogenetic patterns, our results indicate that flowering may be shaped by the different reproductive strategies of Melastomataceae lineages, while fruiting patterns may be governed mainly by the seed dispersal strategy and flowering time, with less phylogenetic influence.